Analysis of thorium fuel feasibility in large scale gas cooled fast reactor using MCNPX code. (January 2018) - Ibrahim, Amr; Aziz, Moustafa; EL-Kameesy, S.U.; EL-Fiki, S.A.; Galahom, A.A.
Highlights: Thorium feasibility as an alternative fuel for the Gas-cooled Fast Reactor has been demonstrated. Thorium core shows acceptable neutronic and safety characteristics. The depressurization and expansion reactivity effects show improvement. GFR2400 thorium-based core can work in both open and closed cycles. GFR2400 thorium-based core can recycle its own MA vector and plutonium of LWRs. Safety-related parameters of thorium core are degraded in equilibrium cycle. Abstract: In this paper thorium fuel feasibility in large scale Gas Cooled Fast Reactor (GCFR) is investigated. The neutronics benchmark used in this study, GFR2400, corresponds to a 2400 MWth GFR concept proposed by the French CEA. MCNPX computational code is used to design a 3D heterogeneous model of the GFR2400 core. A detailed feasibility analysis of the performance of thorium fuel cycle is performed by using thorium as an alternative fertile fuel for the natural uranium vector of the reference core design. The most essential neutronic parameters characterizing the core are determined both for beginning of life (BOL) conditions as well as during burnup. Also, a three-dimensional core cycle-by-cycle simulations is performed to allow explicit characterization of the core behavior and safety-related parameters during both open and equilibrium cycles. The thorium-based core shows favorable neutronic characteristics with an acceptable control and safety parameters for both BOL and open cycle states. The depressurization reactivity effect and core expansion coefficients (axial and radial) show improvement compared to the uranium-based core. However, this improvement is compensated by the deterioration in the effective delayed neutron fraction (β-eff) and the Doppler reactivity Effect. The results of isotopic transmutation and fuel burnup confirm the capability of the core to work in both open and closed cycles and to self-recycle its own MA vector and plutonium of LWRs. However-as is the case in other fast reactors including the uranium-based GFR2400 core, the fuel cycle closure causes safety related parameters to degrade.